1991
DOI: 10.1111/j.1399-3054.1991.tb01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in tomato fruit composition in response to water deficit and salinity

Abstract: Processing tomato (Lycopersicon esculentum Mill. cv. UC82B) plants were subjected to moderate levels of water deficit and salinity (Na2SO4/CaCl2) in sand culture. Fruit water content and the relative contributions of organic and inorganic constituents to fruit solute potential (Ψ) and soluble solids content were determined throughout development. Fruit Ψ averaged –0.63, –0.86 and –0.77 MPa in the control, salinity and water deficit plants, respectively. Reduced net water import and maintenance of solute accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
60
2
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 26 publications
15
60
2
3
Order By: Relevance
“…The major advantage of DI was an improvement in quality in terms of TSS, VC, and acidity [13] . Reduced irrigation treatments (RDI and PRD) resulted in generally improved fruit quality in relation to FI, as reported by Mitchell et al [54] . An ANOVA showed that there was a significant difference in TSS (p<0.05), VC (p<0.05), and TA (p<0.05) of tomato between different treatments in both years.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The major advantage of DI was an improvement in quality in terms of TSS, VC, and acidity [13] . Reduced irrigation treatments (RDI and PRD) resulted in generally improved fruit quality in relation to FI, as reported by Mitchell et al [54] . An ANOVA showed that there was a significant difference in TSS (p<0.05), VC (p<0.05), and TA (p<0.05) of tomato between different treatments in both years.…”
Section: Resultssupporting
confidence: 60%
“…The water stress applied to the crop led to an increase in dry matter and sugar concentrations of ripe fruit. These phenomena have been explained by the fact that water stress did not affect the quantity of dry matter accumulated by the fruit, although it greatly reduces its accumulation of water [54] . Ho et al [55] explained this phenomenon by an increase in the phloem sap concentration, as well as by a decrease in its flux, both resulting from a reduction in the water available in the plant.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, water availability is another crucial factor with a major influence on water and dry matter accumulation in the fruit. While water deficit (whether induced by drought or increased salinity) generally leads to higher dry matter contents, and sugar and acid concentrations (Mizrahi, 1982;Mitchell et al, 1991;Veit-Köhler et al, 1999;Plaut et al, 2004), this is mostly due to a decrease in water influx and thus fresh weight. This means a loss of revenue for the grower and is hence unwanted.…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit due to drought or due to increased salinity (electric conductivity, EC) are known to impact the fruit water and carbon balance differently (Mitchell et al, 1991). However, these particular conditions have not often been studied simultaneously (Mitchell et al, 1991;Plaut et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of plant water status to guarantee a good production and quality of greenhouse tomato (Solanum lycopersicum L.) has been emphasized by many authors (Mitchell et al, 1991;Johnson et al, 1992;Cuartero and Fernandez-Munoz, 1999;De Swaef et al, 2012). Tomato fruit growth results from the influx of water, carbon and minerals through the xylem and the phloem, which is driven by a gradient in hydrostatic and osmotic potential between the stem and the fruit.…”
Section: Introductionmentioning
confidence: 99%